The relation of anti-Mullerian hormone with final menstrual period and menopausal symptoms in the menopausal transition - Kender Erturk, Nergis; Tasgoz, Fatma Nurgul (Annals of Medical Research, 2022)
Aim: To determine the role of anti-mullerian hormone (AMH), menstrual hormones and symptoms in predicting final menstrual period (FMP) in menopausal transition (MT). Materials and Methods: Eighty-two women aged 37-50 years in MT with any degree of menopausal symptoms were included in this prospective study. At the beginning and at the end of two years; serum AMH and menstrual hormone (Follicle stimulating hormone (FSH), luteinizing hormone (LH), estradiol) levels were measured, Menopause Rating Scale (MRS) scores were recorded, then compared. The cut-off of initial AMH level to detect FMP was calculated. Results: Of the 82 patients that were followed for two years, thirty six were in early MT, forty-six were in late MT at the initial. At the end of two years, 15.8 % (13/82) of patients were found to have reached menopause. The rate of AMH decline in two years did not differ significantly between patients who had and did not go through menopause. According to ROC analysis, in patients with menopause the optimal threshold value of baseline AMH to predict FMP over the next 12 months was 0.085ng/ml (area under curve :0.873, 95% CI: 0.726-0.948, p<.001). There was a significant positive correlation between AMH change rate and MRS score change in two years (r=0.462, p<0.001). A significant negative correlation was observed between baseline AMH levels and second year MRS scores (r=- 0.56, p<0.001). Multivariate regression analysis showed no significant independent effect of age, BMI, baseline AMH level, FSH, estradiol, baseline MRS score on AMH change. Conclusion: In MT, serum AMH level and menopausal symptom scores can help predict FMP and assist in the appropriate management of the MT period to provide women with a long-term healthy life.